2008
DOI: 10.1177/154405910808700703
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy Induces Alveolar Bone Regeneration

Abstract: ESWT, extracorporeal shock wave therapy; PCR, polymerase chain-reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 29 publications
1
54
0
2
Order By: Relevance
“…In addition, adequate measures were taken to minimize pain or discomfort to mice during oral infection and sampling. Mice were administered sulfamethoxazole (0.87 mg/ml) and trimethoprim (0.17 mg/ml) daily for 10 days in the drinking water (22), and the oral cavity was swabbed with 0.12% chlorhexidine gluconate (Peridex 3 M; ESPE Dental Products, St. Paul, MN) mouth rinse (19,41) to inhibit the endogenous organisms and to promote subsequent colonization with P. gingivalis, T. denticola, and T. forsythia (19). After a 3-day antibiotic washout period, mice were randomized into two groups, followed by oral infection.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, adequate measures were taken to minimize pain or discomfort to mice during oral infection and sampling. Mice were administered sulfamethoxazole (0.87 mg/ml) and trimethoprim (0.17 mg/ml) daily for 10 days in the drinking water (22), and the oral cavity was swabbed with 0.12% chlorhexidine gluconate (Peridex 3 M; ESPE Dental Products, St. Paul, MN) mouth rinse (19,41) to inhibit the endogenous organisms and to promote subsequent colonization with P. gingivalis, T. denticola, and T. forsythia (19). After a 3-day antibiotic washout period, mice were randomized into two groups, followed by oral infection.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro studies have shown that shock waves have a bactericidal effect on Streptococcus aureus, Streptococcus epidermidis, Pseudomonas aeruginosa, and a MRSA 27065 strain, with decreases in viable numbers of 3 orders of magnitude for certain species [11]. Previous reports have shown that shock wave therapy can kill some oral bacteria and exhibit a beneficial effect during the regeneration process of periodontal disease in a rat model [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Sham-infected control rats received the vehicle (sterile CMC) only. Oral microbial samples obtained from isoflurane-anesthetized rats were collected at pre-and postinfections, as described previously (32,53). In order to monitor the colonization/infection with minimal disruption of the biofilms, a total of 2 postinfection microbial samples (following the fourth and sixth infections) were collected from all infected rats.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, adequate measures were taken to minimize pain or discomfort of rats during oral infection and sampling. Rats were administered kanamycin (20 mg/rat) and ampicillin (20 mg/rat) daily for 4 days in the drinking water (32,33,53), and the oral cavity was swabbed with 0.12% chlorhexidine gluconate (Peridex; 3M Espe Dental Products, St. Paul, MN) mouth rinse (32,53) to inhibit endogenous organisms and to promote subsequent colonization of P. gingivalis. After a 3-day antibiotic washout period, rats were randomized into three groups (n ϭ 9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation